Higher-order Thinking Skills in Teaching Reading Skills at Ethiopian Higher Education: A Qualitative Study on Classroom Practice, and Teachers’ Knowledge and Beliefs - S.G. Gergera; A.G. Tesmand (Психолого-педагогические исследования)
The widespread availability of information and rapid technological advancement are among the significant characteristics of this century. These trends of the century have triggered a paradigm shift in educational goals. As a result, nowadays, to produce active citizens capable of meeting the demands and challenges of the century, developing learners' higher cognitive skills has become a priority in modern education. For instance, in modern language education, improving learners' thinking skills has become one of the responsibilities of language teachers. In line with this concept, this qualitative study aimed to explore English language teachers’ classroom practices, knowledge, and beliefs about integrating higher-order thinking skills in teaching reading skills. Data were collected from four randomly selected English language teachers at Addis Ababa Science and Technology University using observation and interviews. The study’s findings indicate that teachers are less frequently implementing higher-order thinking strategies. However, it has been found that the teachers have a better understanding of higher-order thinking skills and believe that integrating higher-order thinking into teaching English in general and reading skills in particular is among their responsibilities.